Analyzing Factors on Productivity and Marketing Linkage of Maize Value Chain (Journal of Environmental Science and Natural Resources, 2025)
A study was conducted at Sadar Upazilla in Sherpur district, Bangladesh during July 2017 to June 2018 to find out the factors affecting production costs, returns and marketing of maize production. Out of the sample size 55, two separate questionnaires were used for collecting data from producer (30) and market actors (25). Three types of data analysis, namely descriptive statistics (means, percentages and standard deviations), value chain analysis and economic analysis were used for analyzing the collected primary data. From the reviewed theories and empirical works, some factors were identified as influencing maize production; age of the farmer, farmer experience in farming, household income, household education level, cost of labor and number of extension visits. The value chain analysis confirmed that the main actors involved in maize value chain include faria/bepari/assemblers/collectors, wholesalers, retailers. Study revealed that in maize production, the returns of scale of the selected areas were high. So, in the recent time most of the farmers divers from rice to maize production. It was also found that, the opportunity of maize production on an average was high in Sherpur district and farmers had a large scope to increase maize productivity by attaining full efficiency through reallocating the resources. Economic analysis of maize and maize-based cropping pattern in comparison to boro and boro-based cropping pattern indicates the high productivity of maize production system than that of boro rice.Environ. Sci. & Natural Resources, 14(1&2): 37-40, 2025